2023
DOI: 10.1002/ece3.9960
|View full text |Cite
|
Sign up to set email alerts
|

Emigration patterns of motile cryptofauna and their implications for trophic functioning in coral reefs

Abstract: Patterns of movement of marine species can reflect strategies of reproduction and dispersal, species' interactions, trophodynamics, and susceptibility to change, and thus critically inform how we manage populations and ecosystems. On coral reefs, the density and diversity of metazoan taxa are greatest in dead coral and rubble, which are suggested to fuel food webs from the bottom up. Yet, biomass and secondary productivity in rubble is predominantly available in some of the smallest individuals, limiting how a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 101 publications
1
5
0
Order By: Relevance
“…This pattern reflects outcomes anticipated under the intermediate disturbance hypothesis (Connell, 1978), which suggests that species abundance and/or diversity are maximized when the ecological disturbance is neither too low nor high (Dial & Roughgarden, 1998). We speculate that the mid‐exposure site harbors ecological conditions best suited for sessile growth and productivity, including water flow (Gischler, 1997), habitat accessibility (Wolfe, Desbiens, & Mumby, 2023), sedimentation rates (Adam et al, 2015; Logan et al, 2008; Tebbett & Bellwood, 2020), light attenuation (Choi & Ginsburg, 1983) and nutrient profiles (Corredor et al, 1988; Holmes, 1997; Holmes et al, 2000; Nava et al, 2014; Thomas & Atkinson, 1997; Ward‐Paige et al, 2005). However, determining these environmental drivers was beyond the scope of this study and a plethora of alternative hypotheses could be debated, including interactions with other organisms (competition, predation) (Charpy et al, 2012; Cheroske et al, 2000; Gischler, 1997; Meesters et al, 1991) and the age of rubble pieces shaping typical patterns of community succession in rubble (Choi, 1984; Jackson, 1977; Kenyon, 2021; Wulff, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This pattern reflects outcomes anticipated under the intermediate disturbance hypothesis (Connell, 1978), which suggests that species abundance and/or diversity are maximized when the ecological disturbance is neither too low nor high (Dial & Roughgarden, 1998). We speculate that the mid‐exposure site harbors ecological conditions best suited for sessile growth and productivity, including water flow (Gischler, 1997), habitat accessibility (Wolfe, Desbiens, & Mumby, 2023), sedimentation rates (Adam et al, 2015; Logan et al, 2008; Tebbett & Bellwood, 2020), light attenuation (Choi & Ginsburg, 1983) and nutrient profiles (Corredor et al, 1988; Holmes, 1997; Holmes et al, 2000; Nava et al, 2014; Thomas & Atkinson, 1997; Ward‐Paige et al, 2005). However, determining these environmental drivers was beyond the scope of this study and a plethora of alternative hypotheses could be debated, including interactions with other organisms (competition, predation) (Charpy et al, 2012; Cheroske et al, 2000; Gischler, 1997; Meesters et al, 1991) and the age of rubble pieces shaping typical patterns of community succession in rubble (Choi, 1984; Jackson, 1977; Kenyon, 2021; Wulff, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Steep spectral slopes ( b ≤ −1.2), as found across all sites here (groove site excluded), indicate small predator–prey ratios within the rubble interstices (Jennings & Mackinson, 2003; Jennings & Warr, 2003) and high predation risk of larger bodied cryptofauna to predators beyond the measured community (Rassoulzadegan & Sheldon, 1986). Coral rubble biomes are certainly dominated by small‐bodied taxa with low biomass (Wolfe, Desbiens, et al, 2020) and these steep slopes reflect high rubble‐derived productivity of the smallest members of the cryptofauna (Wolfe, Desbiens, & Mumby, 2023). Our data demonstrate that rubble is indeed a lower trophic level haven facilitated by high microhabitat complexity that enhances fine‐scale prey refugia (Heather et al, 2021), as found for epifauna in association with turf and macroalgae (Ape et al, 2018; Fraser et al, 2021b; Fraser, Lefcheck, et al, 2020; Kramer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations